2019
DOI: 10.1055/s-0039-1693701
|View full text |Cite|
|
Sign up to set email alerts
|

Decoration of Fibrin with Extracellular Chaperones

Abstract: Background Many proteins bind to fibrin during clot formation in plasma. We previously identified by mass spectrometry the most abundant proteins that noncovalently bind to fibrin clots. Several of these proteins (e.g., apolipoprotein J/clusterin, haptoglobin, α2-macroglobulin, α1-antitrypsin) can act as extracellular chaperones. Objective We hypothesize that clot-binding proteins may interact with fibrin as chaperones. The goal of this study is to test this hypothesis and to investigate the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Numerous plasma proteins become associated with the fibrin fibers during coagulation of plasma as shown here and in previous studies. [31][32][33] Among the 18 noncovalently and 47 covalently fibrin bound proteins (through cross-linking via FXIIIa) 31,33,42 are albumin, fibronectin, vitronectin, tissue plasminogen activator, plasminogen, lipoprotein(a), α2-antiplasmin, plasminogen activator inhibitor-2 (PAI-2), factor Xa, factor V, tissue factor pathway inhibitor, thrombin-activatable fibrinolysis inhibitor, and VWF. 31,33 Certain plasma proteins such as albumin and fibronectin modulate fibrin formation, structure, and stability by directly interacting with fibrinogen or the fibrin network during fibrin assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous plasma proteins become associated with the fibrin fibers during coagulation of plasma as shown here and in previous studies. [31][32][33] Among the 18 noncovalently and 47 covalently fibrin bound proteins (through cross-linking via FXIIIa) 31,33,42 are albumin, fibronectin, vitronectin, tissue plasminogen activator, plasminogen, lipoprotein(a), α2-antiplasmin, plasminogen activator inhibitor-2 (PAI-2), factor Xa, factor V, tissue factor pathway inhibitor, thrombin-activatable fibrinolysis inhibitor, and VWF. 31,33 Certain plasma proteins such as albumin and fibronectin modulate fibrin formation, structure, and stability by directly interacting with fibrinogen or the fibrin network during fibrin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin generated in plasma by the coagulation cascade binds noncovalently and covalently numerous plasma proteins, [30][31][32][33] and thus differs from fibrin prepared with purified fibrinogen. We therefore compared the effects of anti-GPVI antibodies and inhibitors of GPVI signaling through Syk and Btk on flow-dependent platelet thrombus formation onto fibrins prepared from purified and recombinant fibrinogen, and endogenous fibrin generated by the coagulation cascade in plasma or blood.…”
Section: Introductionmentioning
confidence: 99%
“…The current work on the rupture resistance of fibrin has been performed on blood plasma clots at a physiological fibrin volume fraction, following natural covalent cross-linking by plasma transglutaminase factor XIIIa, and in the presence of all plasma proteins that can potentially modulate fibrin properties (18,19). The rupture resistance of fibrin basically determines the mechanical stability of the entire blood clot because there is not a substantial difference in the mechanical response of human platelet-poor plasma clots, platelet-rich plasma clots, and whole-blood clots (5).…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
“…The cross-β-structures in fibrinogen and fibrin were formed by prolonged heating of plasma (mimicking unfolding that occurs with aging) as well as upon enzymatic conversion of fibrinogen to fibrin, in which formation of β-structures can occur. 1,3 Also, the authors showed an inhibitory effect of caseins (known as milk chaperones) on fibrin formation.…”
mentioning
confidence: 99%
“…In the October issue of Thrombosis and Haemostasis, Talens et al 1 proposed a general physiological role for certain plasma proteins previously shown to bind strongly but noncovalently to fibrinogen and/or fibrin. After excluding the proteins with known hemostatic activities, the authors recognized that some of the remaining fibrin-bound proteins (clusterin, haptoglobin, α2-macroglobulin, apolipoproteins E and AI, albumin, serum amyloid P, and α1-antitrypsin) belong to a family of "extracellular chaperones."…”
mentioning
confidence: 99%